Nanocellulose/palygorskite biocomposite membranes for controlled release of metronidazole - Meneguin, Andréia [UNESP]; Pacheco, Guilherme; Silva, Jhonatan Miguel; de Araujo, Francisca Pereira; Silva-Filho, Edson Cavalcanti; Bertolino, Luiz Carlos; da Silva Barud, Hernane (Elsevier, 2021)
The incorporation of drugs in nanocomposites can be considered a potential strategy for controlled drug release. In this study, a nanocomposite based on bacterial cellulose and the palygorskite clay (BC/PLG) was produced and loaded with metronidazole (MTZ). The samples were characterized using X-ray diffraction (XRD) Spectroscopy, thermal analysis (TG/DTG) and Scanning Electron Microscopy (SEM). The barrier properties were determined to water vapor permeability (WVP). Adsorption tests with PLG were performed using MTZ and drug release profile of the membranes was investigated. The results indicated that PLG increased the crystallinity of the nanocomposites, and greater thermal stability when PLG concentration was 15.0% (BC/PLG15) was observed. WVP of the samples also varied, according to the clay content. Adsorption equilibrium was achieved from 400 mg/L of the PLG and a plateau in the MTZ release rates from BC/PLG was observed after 30 min. Therefore, the results of this study show the potential of these nanocomposite membranes as a platform for controlled drug release.
Keywords: Bacterial cellulose; Clay minerals; Drug release